Studies on year round production of cauliflower (Brassica oleracea var botrytis) under mid hills of Himachal Pradesh - THAKUR, BHUPINDER SINGH (The Indian Journal of Agricultural Sciences, 2014)
Studies were conducted to standardize the optimum time of planting for different varieties of cauliflower under year round quality curd production system during 2009-10 and 2010-11 under mid hills of Himachal Pradesh. The varieties Pusa Himjyoti (early), PSB K -1 (late) and popular hybrids Swati (mid), NS 106 (mid late) were planted at different altitudes (1090 m a msl, 1350 m a msl and 1650m a msl). All the varieties or hybrids planted took more time to curd maturity at higher elevations for irrespective of planting time and maturity group as compared to the lower elevations. Early varieties gave high curd yield under higher temperature conditions, whereas the mid and late varieties gave high curd yield under mild climatic conditions and higher elevations. The June planting date for early group and February planting of mid late group varieties recorded the best benefit: cost ratio under the mid hill conditions. The best planting dates for year round production of cauliflower in the mid hills were therefore found to be June-July (early group); October (late group); followed by February planting of mid or mid late group varieties which can fetch higher returns to the growers besides ensuring best quality curd supply throughout the year to the market.